Computation of transfer function data from frequency response data with application to data-based root-locus. (April 2015) - Hoogendijk, R.; van de Molengraft, M.J.G.; den Hamer, A.J.; Angelis, G.Z.; Steinbuch, M.
Abstract: This paper describes the computation and use of transfer function data (TFD) computed from frequency response data of a system. TFD can be regarded as a sampled, data-based representation of the transfer function. TFD can be computed from frequency response data for stable, lightly damped systems using a Cauchy integral. Computational accuracy and complexity are extensively discussed. As a use-case of TFD it is shown that a root-locus can be computed in a data-based way, using only frequency response data of a system. Experiments on a benchmark motion system demonstrate the use of TFD in minimizing the settling time.